Peran Lembaga Muhammadiyah dalam Mitigasi Bencana di Kabupaten Sinjai - Kiki Rasmala Sani; Syamsuddin (Institut Teknologi Sepuluh Nopember, 2020)
This study aims to analyze the role of the Muhammadiyah Institute in disastermitigation in Sinjai region. As a large organization in Sinjai, Muhammadiyahserves as the government’s partner in promoting disaster preparedness to thepublic via institutions that were founded on the level of Regional Leadershipand the level of business charity. This research uses descriptive analysis withqualitative methods. The respondents were Muhammadiyah Regional Leaders,Muhammadiyah Disaster Management Institutions, and Muhammadiyahcadres in the Sinjai region. The results of this study indicated that theinstitution, since the Regional Leadership of Muhammadiyah Sinjai founded it,had not had a work program. Thus, the agency has not yet significantlycontributed to disaster mitigation. All cadres who exist in the structure of theinstitution are cadres in various other organizations that can be resources inachieving organizational goals